Integrating Civil Participation Into Sustainable Development Practice - Cazabat, Christelle (European Journal of Sustainable Development, 2016)
The Human Development approach introduced in 1990 by the United Nations Development Programme promoted health, education, freedom and civil participation alongside the more traditional increase of income. Twenty-five years later, as income inequalities grow larger in every part of the world, human development is more relevant than ever. Civil participation in particular has become a central element of sustainable development policies such as the Sustainable Development Goals. Since the beginning of the new millennium, beneficiaries have been involved in an increasing number of development projects. Civil participation is being recognized as an asset to sustainable development for several reasons including improved efficiency, fairness and resilience. A review of reports from development practitioners and best practices in the field of civil participation towards sustainable development highlighted the importance of engaging individuals and communities to secure lasting and equitable progress. Yet, in a number of cases, results are not up to expectations and obstacles are hindering the potential of such initiatives. With the aim of reaching the Sustainable Development Goals by 2030, development practitioners can learn from these experiences and integrate civil participation into their programmes more efficiently. Keywords: Civil society, civil participation, human development, development policies, Sustainable Development Goals